Cross-linked polyethylene insulated cable and preparation method thereof

By using a combination of modified linear low-density polyethylene and antioxidants, the synergistic effect of modified mullite whiskers, polyparabenzamide fibers and fluorinated graphite, excellent mechanical properties and thermal aging resistance are prepared by using the combination of modified linear low-density polyethylene and antioxidants. The crosslinked polyethylene insulated cable solves the problems of poor wear resistance and insufficient thermal aging performance of crosslinked polyethylene insulated cables in the prior art.

CN118755187BActive Publication Date: 2025-02-25SHANDONG ZHONGTIAN CABLE TECH CO LTD

Patent Information

Application Number
CN202411242347.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-05
Publication Date
2025-02-25
Estimated Expiration
2044-09-05

AI Technical Summary

Technical Problem

Existing crosslinked polyethylene insulated cables have poor wear resistance during long-term use, which is susceptible to tree contact, and is prone to thermal aging, resulting in low service life.

Method used

The crosslinked polyethylene insulated cable is prepared by a combination of material A and material B. Material A is made of modified linear low-density polyethylene, 2,5-dimethyl-2,5-bis(tert-butylperoxy)hexane , bistert-butyl peroxide isopropylbenzene, vinyl tris(2-methoxyethoxy)silane and 1,2-polybutadiene. The material B is composed of linear low-density polyethylene and dilauric acid. The combination of butyltin and antioxidants improves the thermal aging and mechanical properties of crosslinked polyethylene by modifying the synergistic effects of mullite whiskers, polyparabenzamide fibers and fluorinated graphite.

Benefits of technology

The excellent mechanical properties and heat-resistant aging performance of cross-linked polyethylene insulated cables are achieved, which extends the service life and improves the wear resistance and scorching resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The present invention belongs to the technical field of polyethylene preparation, and specifically relates to a cross-linked polyethylene insulated cable and a preparation method thereof. The cross-linked polyethylene insulated cable is composed of material A and material B, and the weight ratio of material A to material B is 95:5; material A is composed of the following raw materials: modified linear low-density polyethylene, 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane, di-tert-butylperoxyisopropylbenzene, vinyl tri(2-methoxyethoxy)silane, 1,2-polybutadiene; material B is composed of the following raw materials: linear low-density polyethylene, dibutyltin dilaurate, and antioxidant. In the cross-linked polyethylene insulated cable of the present invention, material A interacts with material B, so that the finally prepared cross-linked polyethylene insulated cable has excellent mechanical properties, chemical stability, and heat aging resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of polyethylene preparation, and specifically relates to a cross-linked polyethylene insulated cable and a preparation method thereof. Background Art

[0002] The functions of power cables include the transmission and distribution of electrical energy. They are often used in urban power grids, power station lead-out lines, underwater transmission lines and other fields. Power cables are mainly composed of conductors, insulation layers, shielding layers, sheaths and armor. Among them, the conductor is usually made of metal materials such as copper or aluminum with good conductivity; and the role of the insulation layer is to isolate the conductor from the external environment and the conductor from each other, and it needs to have excellent electrical properties. Polyethylene is widely used as a cable insulation material because of its excellent chemical resistance and electrical insulation. In the large category of polyethylene, cross-linked polyethylene is widely used in the manufacture of insulating cable materials because of its good heat resistance, high mechanical strength, relatively simple structure, light weight and chemical corrosion resistance.

[0003] At present, the preparation methods of cross-linked polyethylene mainly include peroxide cross-linking, radiation cross-linking and silane cross-linking. Silane cross-linked polyethylene is made by introducing cross-linkable alkoxysilanes into the polyethylene main chain by grafting or copolymerization. Since silane cross-linking does not require special cross-linking equipment, the process control is relatively simple, and the electrical properties are excellent, it solves the problems of low melting temperature and expansion coefficient of traditional polyethylene, large shrinkage, and easy deformation and damage of insulation. Therefore, it has unparalleled advantages in the field of medium and low voltage wires and cables. However, due to the poor wear resistance of overhead insulated cables, long-term contact with trees will cause insulation thinning, and the cables are prone to thermal aging, resulting in a low service life. Therefore, it is urgent to explore a new type of cross-linked polyethylene insulated cable. Summary of the invention

[0004] The purpose of the present invention is to provide a cross-linked polyethylene insulated cable. The cross-linked polyethylene insulated cable has excellent mechanical properties and heat aging resistance. The present invention also provides a preparation method thereof.

[0005] The cross-linked polyethylene insulated cable of the present invention is composed of material A and material B, wherein the weight ratio of material A to material B is 95:5; material A is composed of the following raw materials in parts by weight: 100 parts of modified linear low-density polyethylene, 0.15-0.17 parts of 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane, 0.03-0.05 parts of di-tert-butylperoxyisopropylbenzene, 2.3-2.5 parts of vinyl tri(2-methoxyethoxy)silane, and 0.05-0.08 parts of 1,2-polybutadiene; material B is composed of the following raw materials in parts by weight: 100 parts of linear low-density polyethylene, 0.40-0.45 parts of dibutyltin dilaurate, and 0.05-0.08 parts of an antioxidant;

[0006] Wherein: the preparation method of the modified linear low-density polyethylene in material A comprises the following steps:

[0007] ① The mullite whiskers were ultrasonically dispersed in an isopropanol solution for 33-35 minutes, and then 3-aminopropyltriethoxysilane was added and stirred at 75-78°C for 3.8 hours. The product was centrifuged and washed with alcohol for 3-4 times. Finally, the obtained precipitate was vacuum dried at 73-75°C for 24 hours to prepare modified mullite whiskers;

[0008] ② After mixing the modified mullite whisker, polyphenylamide fiber, fluorinated graphite and linear low-density polyethylene in a mixer, take out the billet, put the billet into a 113-115°C vulcanizer, increase the pressure by 5MPa every 10 minutes until the pressure reaches 20MPa, then increase the temperature of the vulcanizer to 175-178°C for cross-linking, and naturally cool to room temperature after cross-linking to prepare the modified linear low-density polyethylene.

[0009] Wherein: the mass of 3-aminopropyltriethoxysilane in step ① accounts for 4% of the mass of mullite whiskers.

[0010] In step ①, the mass ratio of 3-aminopropyltriethoxysilane to isopropanol solution is 1:4.

[0011] In step ①, the alcohol washing adopts isopropanol solution.

[0012] In step ②, the mass ratio of the modified mullite whisker, poly(p-phenylene amide) fiber and graphite fluoride to the linear low-density polyethylene is 1:50-52.

[0013] In step ②, the mass ratio of modified mullite whisker, poly(p-phenylene amide) fiber and graphite fluoride is 0.6-0.8:1:0.3-0.5.

[0014] In step ②, the cross-linking pressure is 20 MPa and the cross-linking time is 12-15 min.

[0015] The antioxidant in component B is a mixture of N-(4-anilinophenyl)maleimide and 4,4'-thiobis(6-tert-butyl-3-methylphenol), and the mass ratio of the two is 1:1.

[0016] The method for preparing the cross-linked polyethylene insulated cable of the present invention comprises the following steps:

[0017] (1) melt-grafting modified linear low-density polyethylene, 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane, di-tert-butylperoxyisopropylbenzene, vinyl tri(2-methoxyethoxy)silane and 1,2-polybutadiene to prepare material A;

[0018] (2) uniformly mixing linear low-density polyethylene, dibutyltin dilaurate and an antioxidant, adding the mixture into an internal mixer for mixing, and preparing material B;

[0019] (3) Material A and material B are mixed evenly at room temperature, then melt-mixed, and the discharged materials are pressed into sheets on a vulcanizer, and finally cross-linked to prepare a cross-linked polyethylene insulated cable.

[0020] in:

[0021] During the melt grafting in step (1), the rotation speed of the melting machine is 25-30 r / min, the melt grafting time is 13-15 min, and the melt grafting temperature is 175-180°C.

[0022] In step (2), the mixing temperature is 170-180° C. and the mixing time is 10-15 min.

[0023] In step (3), the melt mixing temperature is 180-183°C, and the melt mixing time is 12-15 minutes.

[0024] In step (3), the tableting pressure of the vulcanizing machine is 20 MPa, the tableting temperature is 180-183° C., and the tableting time is 6-8 min.

[0025] The cross-linking in step (3) is carried out in water at 75-80°C for 8.5-8.8 hours.

[0026] Compared with the prior art, the present invention has the following beneficial effects:

[0027] (1) In the cross-linked polyethylene insulated cable described in the present invention, material A interacts with material B, and material B plays a catalytic role. In material A, modified linear low-density polyethylene is used as the main component, and the linear low-density polyethylene is modified by a mixture of modified mullite whiskers, poly(p-phenylene amide) fibers and fluorinated graphite, so as to improve the heat aging resistance of the cross-linked polyethylene finally prepared, and at the same time make it have excellent mechanical properties and chemical stability. 2,5-Dimethyl-2,5-di(tert-butylperoxy)hexane and di-tert-butylperoxyisopropylbenzene are used as initiators to improve the cross-linking efficiency, and vinyl tri(2-methoxyethoxy)silane is used as the main cross-linking agent. The hydrolysis degree of the main cross-linking agent is moderate, thereby avoiding decomposition before uniform mixing, causing local cross-linking and forming an uneven cross-linking structure. By introducing the auxiliary cross-linking agent 1,2-polybutadiene, its own unsaturated double bonds are used to participate in the addition reaction to assist cross-linking and increase the cross-linking density. Therefore, the raw materials in material A work synergistically to fundamentally guarantee the mechanical properties and heat aging resistance of the prepared cross-linked polyethylene insulated cable.

[0028] (2) In the cross-linked polyethylene insulated cable described in the present invention, the modified linear low-density polyethylene is the main component in the material A. Compared with low-density polyethylene, the linear low-density polyethylene has greater strength and rigidity, better toughness, and higher tensile strength and elongation at break. Therefore, it can withstand higher operating temperatures. Since there are a large number of randomly distributed short branches in the linear low-density polyethylene, it is conducive to the chain extension reaction, so it is more conducive to the formation of a network structure with a high cross-linking density. In order to make the network structure of the linear low-density polyethylene after cross-linking with silane have better mechanical properties and heat aging resistance, the linear low-density polyethylene is first modified by a mixture of modified mullite whiskers, polyparabenzamide fibers and fluorinated graphite, wherein the mullite whiskers have a nucleation effect on the linear low-density polyethylene, which is conducive to the formation of crystals. After being modified with a silane coupling agent, it is evenly dispersed in the linear low-density polyethylene, thereby maximally improving the toughness and chemical stability of the linear low-density polyethylene. Polyparabenzamide fiber is an organic fiber with high strength, high modulus, low density and high temperature resistance. Only a small amount of it can enhance the strength and high temperature resistance of linear low-density polyethylene. Fluorinated graphite itself has low surface energy and interlayer energy and good hydrophobicity, and acts as a solid lubricant during the friction process, making the prepared cross-linked polyethylene have excellent wear resistance. Therefore, the modified mullite whiskers, polyparabenzamide fibers and fluorinated graphite work synergistically to give the modified linear low-density polyethylene excellent properties.

[0029] (3) In the cross-linked polyethylene insulated cable described in the present invention, an antioxidant is added to the material B, and a mixture of N-(4-anilinophenyl)maleimide and 4,4'-thiobis(6-tert-butyl-3-methylphenol) is selected as the antioxidant. The two act synergistically to more significantly inhibit the thermal oxidation aging of the carbonyl group formed in the cross-linked polyethylene without reducing the degree of cross-linking, thereby improving the scorch resistance of the cross-linked polyethylene.

[0030] (4) The method for preparing the cross-linked polyethylene insulated cable of the present invention has a simple process and is easy to implement. The prepared cross-linked polyethylene insulated cable has stable performance. DETAILED DESCRIPTION

[0031] The present invention is further described below with reference to the embodiments.

[0032] Example 1

[0033] The cross-linked polyethylene insulated cable described in Example 1 is composed of material A and material B, and the weight ratio of material A to material B is 95:5; material A is composed of the following raw materials in parts by weight: 100 parts of modified linear low-density polyethylene, 0.16 parts of 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane, 0.04 parts of di-tert-butylperoxyisopropylbenzene, 2.4 parts of vinyl tri(2-methoxyethoxy)silane, and 0.07 parts of 1,2-polybutadiene; material B is composed of the following raw materials in parts by weight: 100 parts of linear low-density polyethylene, 0.43 parts of dibutyltin dilaurate, and 0.06 parts of antioxidant;

[0034] Wherein: the preparation method of the modified linear low-density polyethylene in material A comprises the following steps:

[0035] ① The mullite whiskers were ultrasonically dispersed in an isopropanol solution for 34 minutes, and then 3-aminopropyltriethoxysilane was added and stirred at 76°C for 3.8 hours. The product was centrifuged and washed with alcohol for 4 times. Finally, the obtained precipitate was vacuum dried at 74°C for 24 hours to prepare modified mullite whiskers;

[0036] ② After the modified mullite whisker, poly(p-phenylene amide) fiber, graphite fluoride and linear low-density polyethylene are mixed in a mixer, the billet is taken out and placed in a 114°C vulcanizer. The pressure is increased by 5 MPa every 10 minutes until it reaches 20 MPa. The temperature of the vulcanizer is then increased to 176°C for cross-linking. After the cross-linking is completed, it is naturally cooled to room temperature to prepare the modified linear low-density polyethylene.

[0037] Wherein: the mass of 3-aminopropyltriethoxysilane in step ① accounts for 4% of the mass of mullite whiskers.

[0038] In step ①, the mass ratio of 3-aminopropyltriethoxysilane to isopropanol solution is 1:4.

[0039] In step ①, the alcohol washing adopts isopropanol solution.

[0040] In step ②, the mass ratio of the modified mullite whisker, poly(p-phenylene amide) fiber, and graphite fluoride to the linear low-density polyethylene is 1:50.

[0041] In step ②, the mass ratio of modified mullite whisker, poly(p-phenylene amide) fiber and graphite fluoride is 0.7:1:0.4.

[0042] In step ②, the cross-linking pressure is 20 MPa and the cross-linking time is 13 min.

[0043] The antioxidant in component B is a mixture of N-(4-anilinophenyl)maleimide and 4,4'-thiobis(6-tert-butyl-3-methylphenol), and the mass ratio of the two is 1:1.

[0044] The method for preparing the cross-linked polyethylene insulated cable described in this embodiment 1 comprises the following steps:

[0045] (1) melt-grafting modified linear low-density polyethylene, 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane, di-tert-butylperoxyisopropylbenzene, vinyl tri(2-methoxyethoxy)silane and 1,2-polybutadiene to prepare material A;

[0046] (2) uniformly mixing linear low-density polyethylene, dibutyltin dilaurate and an antioxidant, adding the mixture into an internal mixer for mixing, and preparing material B;

[0047] (3) Material A and material B are mixed evenly at room temperature, then melt-mixed, and the discharged materials are pressed into sheets on a vulcanizer, and finally cross-linked to prepare a cross-linked polyethylene insulated cable.

[0048] in:

[0049] During the melt grafting in step (1), the speed of the melting machine is 27 r / min, the melt grafting time is 14 min, and the melt grafting temperature is 177°C.

[0050] In step (2), the mixing temperature is 175° C. and the mixing time is 13 min.

[0051] In step (3), the melt mixing temperature is 182° C. and the melt mixing time is 13 min.

[0052] In step (3), the tableting pressure of the vulcanizing machine is 20 MPa, the tableting temperature is 182° C., and the tableting time is 7 min.

[0053] The cross-linking in step (3) is carried out in water at 77°C for 8.7 hours.

[0054] Example 2

[0055] The cross-linked polyethylene insulated cable described in Example 2 is composed of material A and material B, and the weight ratio of material A to material B is 95:5; material A is composed of the following raw materials in parts by weight: 100 parts of modified linear low-density polyethylene, 0.15 parts of 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane, 0.05 parts of di-tert-butylperoxyisopropylbenzene, 2.3 parts of vinyl tri(2-methoxyethoxy)silane, and 0.08 parts of 1,2-polybutadiene; material B is composed of the following raw materials in parts by weight: 100 parts of linear low-density polyethylene, 0.40 parts of dibutyltin dilaurate, and 0.05 parts of antioxidant;

[0056] Wherein: the preparation method of the modified linear low-density polyethylene in material A comprises the following steps:

[0057] ① The mullite whiskers were ultrasonically dispersed in an isopropanol solution for 33 minutes, and then 3-aminopropyltriethoxysilane was added and stirred at 75°C for 3.8 hours. The product was centrifuged and washed with alcohol three times. Finally, the obtained precipitate was vacuum dried at 73°C for 24 hours to prepare modified mullite whiskers;

[0058] ② After the modified mullite whisker, poly(p-phenylene amide) fiber, graphite fluoride and linear low-density polyethylene are mixed in a mixer, the billet is taken out and placed in a 113°C vulcanizer. The pressure is increased by 5 MPa every 10 minutes until it reaches 20 MPa. The temperature of the vulcanizer is then increased to 175°C for cross-linking. After the cross-linking is completed, it is naturally cooled to room temperature to prepare the modified linear low-density polyethylene.

[0059] Wherein: the mass of 3-aminopropyltriethoxysilane in step ① accounts for 4% of the mass of mullite whiskers.

[0060] In step ①, the mass ratio of 3-aminopropyltriethoxysilane to isopropanol solution is 1:4.

[0061] In step ①, the alcohol washing adopts isopropanol solution.

[0062] In step ②, the mass ratio of the modified mullite whisker, poly(p-phenylene amide) fiber, and graphite fluoride to the linear low-density polyethylene is 1:51.

[0063] In step ②, the mass ratio of modified mullite whisker, poly(p-phenylene amide) fiber and graphite fluoride is 0.6:1:0.5.

[0064] In step ②, the cross-linking pressure is 20 MPa and the cross-linking time is 12 min.

[0065] The antioxidant in component B is a mixture of N-(4-anilinophenyl)maleimide and 4,4'-thiobis(6-tert-butyl-3-methylphenol), and the mass ratio of the two is 1:1.

[0066] The method for preparing the cross-linked polyethylene insulated cable described in this embodiment 2 comprises the following steps:

[0067] (1) melt-grafting modified linear low-density polyethylene, 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane, di-tert-butylperoxyisopropylbenzene, vinyl tri(2-methoxyethoxy)silane and 1,2-polybutadiene to prepare material A;

[0068] (2) uniformly mixing linear low-density polyethylene, dibutyltin dilaurate and an antioxidant, adding the mixture into an internal mixer for mixing, and preparing material B;

[0069] (3) Material A and material B are mixed evenly at room temperature, then melt-mixed, and the discharged materials are pressed into sheets on a vulcanizer, and finally cross-linked to prepare a cross-linked polyethylene insulated cable.

[0070] in:

[0071] During the melt grafting in step (1), the speed of the melting machine is 25 r / min, the melt grafting time is 13 min, and the melt grafting temperature is 175°C.

[0072] In step (2), the mixing temperature is 170° C. and the mixing time is 10 min.

[0073] In step (3), the melt mixing temperature is 180° C. and the melt mixing time is 12 min.

[0074] In step (3), the tableting pressure of the vulcanizing machine is 20 MPa, the tableting temperature is 180° C., and the tableting time is 6 min.

[0075] The cross-linking in step (3) is carried out in water at 75°C for 8.5 hours.

[0076] Example 3

[0077] The cross-linked polyethylene insulated cable described in Example 3 is composed of material A and material B, and the weight ratio of material A to material B is 95:5; material A is composed of the following raw materials in parts by weight: 100 parts of modified linear low-density polyethylene, 0.17 parts of 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane, 0.03 parts of di-tert-butylperoxyisopropylbenzene, 2.5 parts of vinyl tri(2-methoxyethoxy)silane, and 0.05 parts of 1,2-polybutadiene; material B is composed of the following raw materials in parts by weight: 100 parts of linear low-density polyethylene, 0.45 parts of dibutyltin dilaurate, and 0.08 parts of antioxidant;

[0078] Wherein: the preparation method of the modified linear low-density polyethylene in material A comprises the following steps:

[0079] ① The mullite whiskers were ultrasonically dispersed in an isopropanol solution for 35 minutes, and then 3-aminopropyltriethoxysilane was added and stirred at 78°C for 3.8 hours. The product was centrifuged and washed with alcohol for 4 times. Finally, the obtained precipitate was vacuum dried at 75°C for 24 hours to prepare modified mullite whiskers;

[0080] ② After the modified mullite whisker, poly(p-phenylene amide) fiber, graphite fluoride and linear low-density polyethylene are mixed in a mixer, the billet is taken out and placed in a 115°C vulcanizer. The pressure is increased by 5 MPa every 10 minutes until it reaches 20 MPa. The temperature of the vulcanizer is then increased to 178°C for cross-linking. After the cross-linking is completed, it is naturally cooled to room temperature to prepare the modified linear low-density polyethylene.

[0081] Wherein: the mass of 3-aminopropyltriethoxysilane in step ① accounts for 4% of the mass of mullite whiskers.

[0082] In step ①, the mass ratio of 3-aminopropyltriethoxysilane to isopropanol solution is 1:4.

[0083] In step ①, the alcohol washing adopts isopropanol solution.

[0084] In step ②, the mass ratio of the modified mullite whisker, poly(p-phenylene amide) fiber, and graphite fluoride to the linear low-density polyethylene is 1:52.

[0085] In step ②, the mass ratio of modified mullite whisker, poly(p-phenylene amide) fiber and graphite fluoride is 0.8:1:0.3.

[0086] In step ②, the cross-linking pressure is 20 MPa and the cross-linking time is 15 min.

[0087] The antioxidant in component B is a mixture of N-(4-anilinophenyl)maleimide and 4,4'-thiobis(6-tert-butyl-3-methylphenol), and the mass ratio of the two is 1:1.

[0088] The method for preparing the cross-linked polyethylene insulated cable described in this embodiment 3 comprises the following steps:

[0089] (1) melt-grafting modified linear low-density polyethylene, 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane, di-tert-butylperoxyisopropylbenzene, vinyl tri(2-methoxyethoxy)silane and 1,2-polybutadiene to prepare material A;

[0090] (2) uniformly mixing linear low-density polyethylene, dibutyltin dilaurate and an antioxidant, adding the mixture into an internal mixer for mixing, and preparing material B;

[0091] (3) Material A and material B are mixed evenly at room temperature, then melt-mixed, and the discharged materials are pressed into sheets on a vulcanizer, and finally cross-linked to prepare a cross-linked polyethylene insulated cable.

[0092] in:

[0093] During the melt grafting in step (1), the speed of the melting machine is 30 r / min, the melt grafting time is 15 min, and the melt grafting temperature is 180°C.

[0094] In step (2), the mixing temperature is 180° C. and the mixing time is 15 min.

[0095] In step (3), the melt mixing temperature is 183° C. and the melt mixing time is 15 min.

[0096] In step (3), the tableting pressure of the vulcanizing machine is 20 MPa, the tableting temperature is 183° C., and the tableting time is 8 min.

[0097] The cross-linking in step (3) is carried out in water at 80°C for 8.8 hours.

[0098] Comparative Example 1

[0099] The preparation method and raw material composition of the cross-linked polyethylene insulated cable described in this comparative example 1 are the same as those in Example 1. The only difference is that the modified linear low-density polyethylene in the cross-linked polyethylene insulated cable material A described in comparative example 1 is different. During the modification, only polyparabenzamide fiber and fluorinated graphite are added to modify the linear low-density polyethylene.

[0100] Comparative Example 2

[0101] The preparation method and raw material composition of the cross-linked polyethylene insulated cable described in this comparative example 2 are the same as those in Example 1. The only difference is that the modified linear low-density polyethylene in the cross-linked polyethylene insulated cable material A described in comparative example 2 is different. During the modification, only modified mullite whiskers and fluorinated graphite are added to modify the linear low-density polyethylene.

[0102] Comparative Example 3

[0103] The preparation method and raw material composition of the cross-linked polyethylene insulated cable described in this comparative example 3 are the same as those in Example 1. The only difference is that the modified linear low-density polyethylene in the cross-linked polyethylene insulated cable material A described in comparative example 3 is different. During the modification, only modified mullite whiskers and polyparabenzamide fibers are added to modify the linear low-density polyethylene.

[0104] The cross-linked polyethylene insulated cables prepared in Examples 1-3 and Comparative Examples 1-3 were subjected to performance tests, wherein the tensile strength and elongation at break test standards were both based on GB / T 1040-1992 "Test Methods for Tensile Properties of Plastics", and the aging test was based on GB / T2951.2-1997 "General Test Methods for Cable Insulation and Sheath Materials Part 1: General Test Methods Section 2: Thermal Aging Test Methods"; the test results are shown in Table 1 below:

[0105] Table 1 Performance test results of cross-linked polyethylene insulated cables

[0106]

Claims

1. A cross-linked polyethylene insulated cable, characterized in that: The invention is composed of material A and material B, wherein the weight ratio of material A to material B is 95:5; material A is composed of the following raw materials in parts by weight: 100 parts of modified linear low-density polyethylene, 0.15-0.17 parts of 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane, 0.03-0.05 parts of di-tert-butylperoxyisopropylbenzene, 2.3-2.5 parts of vinyl tri(2-methoxyethoxy)silane, and 0.05-0.08 parts of 1,2-polybutadiene; material B is composed of the following raw materials in parts by weight: 100 parts of linear low-density polyethylene, 0.40-0.45 parts of dibutyltin dilaurate, and 0.05-0.08 parts of an antioxidant; Wherein: the preparation method of the modified linear low-density polyethylene in material A comprises the following steps: ① The mullite whiskers were ultrasonically dispersed in an isopropanol solution for 33-35 minutes, and then 3-aminopropyltriethoxysilane was added and stirred at 75-78°C for 3.8 hours. The product was centrifuged and washed with alcohol for 3-4 times. Finally, the obtained precipitate was vacuum dried at 73-75°C for 24 hours to prepare modified mullite whiskers; ② After the modified mullite whisker, polyphenylene amide fiber, fluorinated graphite and linear low-density polyethylene are mixed in a mixer, the blank is taken out, and the blank is placed in a 113-115°C vulcanizer, and the pressure is increased by 5MPa every 10 minutes until the pressure is increased to 20MPa, and then the temperature of the vulcanizer is increased to 175-178°C for cross-linking. After the cross-linking is completed, it is naturally cooled to room temperature to prepare a modified linear low-density polyethylene; in: In step ②, the mass ratio of the modified mullite whisker, poly(p-phenylene amide) fiber, and graphite fluoride to the linear low-density polyethylene is 1:50-52; In step ②, the mass ratio of modified mullite whisker, poly(p-phenylene amide) fiber and graphite fluoride is 0.6-0.8:1:0.3-0.5; In step ②, the cross-linking pressure is 20 MPa and the cross-linking time is 12-15 min.

2. The cross-linked polyethylene insulated cable according to claim 1, characterized in that: In step ①, the mass of 3-aminopropyltriethoxysilane accounts for 4% of the mass of the mullite whisker; In step ①, the mass ratio of 3-aminopropyltriethoxysilane to isopropanol solution is 1:4; In step ①, the alcohol washing adopts isopropanol solution.

3. The cross-linked polyethylene insulated cable according to claim 1, characterized in that: The antioxidant in component B is a mixture of N-(4-anilinophenyl)maleimide and 4,4'-thiobis(6-tert-butyl-3-methylphenol), and the mass ratio of the two is 1:

1.

4. A method for preparing a cross-linked polyethylene insulated cable according to claim 1, characterized in that: It consists of the following steps: (1) melt-grafting modified linear low-density polyethylene, 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane, di-tert-butylperoxyisopropylbenzene, vinyl tri(2-methoxyethoxy)silane and 1,2-polybutadiene to prepare material A; (2) uniformly mixing linear low-density polyethylene, dibutyltin dilaurate and an antioxidant, adding the mixture into an internal mixer for mixing, and preparing material B; (3) Material A and material B are mixed evenly at room temperature, then melt-mixed, and the discharged materials are pressed into sheets on a vulcanizer, and finally cross-linked to prepare a cross-linked polyethylene insulated cable.

5. The method for preparing a cross-linked polyethylene insulated cable according to claim 4, characterized in that: During the melt grafting in step (1), the rotation speed of the melting machine is 25-30 r / min, the melt grafting time is 13-15 min, and the melt grafting temperature is 175-180°C.

6. The method for preparing a cross-linked polyethylene insulated cable according to claim 4, characterized in that: In step (2), the mixing temperature is 170-180° C. and the mixing time is 10-15 min.

7. The method for preparing a cross-linked polyethylene insulated cable according to claim 4, characterized in that: In step (3), the melt mixing temperature is 180-183°C, and the melt mixing time is 12-15 minutes.

8. The method for preparing a cross-linked polyethylene insulated cable according to claim 4, characterized in that: In step (3), the tableting pressure of the vulcanizing machine is 20 MPa, the tableting temperature is 180-183° C., and the tableting time is 6-8 min.

9. The method for preparing a cross-linked polyethylene insulated cable according to claim 4, characterized in that: The cross-linking in step (3) is carried out in water at 75-80°C for 8.5-8.8 hours.

Citation Information

Patent Citations

  • Method for preparing silane modified peroxide crosslinked polyetylene water-tree-retardant insulating materials

    CN101362813A

  • Functional master batch for improving heat resistance of polyethylene

    CN107011560A

Cited By

  • Crosslinked polyethylene insulated power anti-interference control cable and support thereof

    CN120545012A